Partisipasi Pemuda Karang Taruna dalam Kegiatan Sosial di Desa Sidoagung - Dimasendra Bagas Wicaksana; Syifa Adha Kamelia; Rhika Rhiffayanty; Adek Bibit Sayekti; Erni Saharuddin (Universitas Medan Area, 2026)
This study aims to examine the role of the government in increasing youth social participation through Karang Taruna in Senuko Hamlet, Sidoagung Village based on Marschall's social participation theory. The focus of the study includes the existence of participatory groups, the community's ability to engage in the process, and the existence of a space for expressing opinions in decision-making. Youth participation in social activities is a fundamental element in sustainable village development. This study uses a qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation of Karang Taruna administrators, village government officials, and community leaders. The results of the study show that youth social participation has been successful in two indicators, namely the existence of participatory groups and the ability to get involved, but is still weak in terms of expressing opinions in the decision-making process. Therefore, improving the communication system, transparency of information, and resource support are key to optimising the contribution of youth as agents of inclusive and sustainable village development.